Ecological Study on Factors Related to the Mortality of Rabies in North Sulawesi Province at the Year of 2015 to 2017 - Machmud, Putri Bungsu; Tiarma, Noer Syafiiah (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Indonesia, which is part of the region, contributes 25 provinces including areas that have not been free from the endemic of rabies. One of the provinces that ranked top in the cases of rabies was North Sulawesi. Therefore, this study aims to find correlations between factors related to the prevalence of rabies deaths in North Sulawesi Province in 2015 - 2017. This study used a mixed ecological study design by applying the principle of total sampling to 15Ã‚Â districts/citiesin North Sulawesi. The results of the study found that there was a negative and weak strength correlation on theÃ‚Â anti rabiesvaccine coverage factor (r = 0.279), moderate strength correlation on the ratio of health care workers (r = 0.345), and the ratio of health care facilities (r = 0.320) to the mortality of rabies. While the sex ratio factor is positive and has moderate strength (r = 0.365) against the mortality of rabies. The new findings of health care facility and health care workers that have a moderate strength correlation need to be included in the prevention of rabies approach because it can help to facilitate washing wounds treatment.Ã‚Â